Analysis of Financing Risk Management and Mitigation Strategies on the Performance of Islamic Banks - Naufal Luthfi Rahman; Febryanto Safrizal (Pasca Sarjana UKI, 2025)
This study aims to analyze the application of financing risk management and mitigation strategies implemented by Islamic banks in maintaining their financial stability and performance. Using a qualitative descriptive approach with the case study method, data is collected through literature studies from various relevant sources, such as scientific journals, books and official documents. The results of the study show that Islamic banks face various risks, including contract risks, returns, investments, and strategic risks, which arise due to operational characteristics based on sharia principles. To anticipate potential risks of non-performing financing, Islamic banks implement mitigation strategies through financing feasibility analysis, the 5C principle. In addition, challenges in the era of digital transformation, such as the threat of cyberattacks and regulatory changes, encourage Islamic banks to strengthen internal control systems and increase technological readiness. These findings reinforce the understanding that effective risk management contributes positively to the asset quality and sustainability of Islamic banks' performance amid changing business dynamics